Fragilidade ambiental associada à conectividade do escoamento superficial indireto na bacia do Rio Pirajibu-Mirim, Sorocaba/SP - Marques, Valteir Vieira [UNESP] (2017)
The urgent need of the human population, especially in the last four decades, in seeking resources to provide its quantitative and qualitative growth, has intensified the processes of environmental degradation. Among these, erosion processes and sediment transport deserve special attention because they limit the very development of humanity. For sustainable development to occur there must be appropriate planning and management of land use and occupation integrated with the natural physical conditions of each area. However, one of the major shortcomings for managers and planners is the deficiency of cartographic products that identify priority areas for containment of degradation processes, as well as to restrict what currently vulnerable areas are becoming highly vulnerable by new uses and occupation. The studies of environmental fragility, due to its systemic characteristics of integration of natural environments and anthropic interventions have been indicated as a good reference to subsidize environmental planning and management. In this work, surface flow distance mapping was integrated with the methodology of empirical fragility proposed by Ross (1994). The final cartographic product, considering the effects of surface runoff, presents greater hydrosedimentological consistency. The final result allows to easily identify the priority areas that need greater attention for actions of control and containment of erosive processes and sediment production. It also provides due emphasis to the impacts caused by linear structures, especially the road system, an important contributor to the production and transfer of sediments to surface waters, which is not possible only with the map of emerging fragility.